SUMMARY OF RECYCLING PROCESSES AND REUSE OF WET-BLUE SCRAPING WASTE - Flores-Tapia, Nelly (2023)
Tanneries are highly polluting industries that release dangerous compounds, such as chromium, in their solid, liquid, and other contaminant in its gaseous effluents. According to the bibliography, all solid discharges end up in landfills; meanwhile, the liquid effluents are treated and then disposed of in the closest rivers. It is essential to develop eco-sustainable and innovative technologies to manage and dispose of this waste. However, as wet-blue is chemically stable, the development of new technologies for recycling or reusing tannery waste is becoming a great challenge for researchers. Those responsible for studying these residues have begun to use this waste to produce new materials that simulate leather qualities or technologies that allow collagen to be extracted from wet-blue most economically. Several works on leather waste management reviewed for this summary report concisely the processes used to reuse or recycle wet-blue. Then this review reports, for the first time, the state of the art of strategies related to the recovery and valorization of these leather and hydrolyzed collagen residues. In the conclusion section, the authors provide practical implications for the industry regarding wet-blue recycling.